Virtual Library Management Model - Rubiyo, Rubiyo; Fakhruddin, Fakhruddin; Yulianto, Arief (Proceedings of International Conference on Science, Education, and Technology, 2024)
The library of the Police Academy (Akpol) plays a very important role in supporting the smooth learning activities of the cadets. However, the Akpol library currently still uses a conventional or manual system in management, providing library services, cataloguing books, borrowing, returning, and searching for information is done manually. Article 24 of law number 43 of 2007 concerning the development of higher education libraries that must be based on technology and information. Libraries with conventional systems cause various obstacles, especially access, limited access to information, low efficiency and cause cadets to have to come physically to the library besides having the risk of recording errors. In addition to not utilising and using information technology, it makes it difficult to monitor and evaluate the use of the Akpol library collection, which ultimately has an impact on the teaching and learning process. Article 14 paragraph 3 of Law number 43 of 2007 where the manager is obliged to develop library services using technology and information. This research uses a literature study method to identify the problems faced by Akpol library managers who have not used information technology and provide recommendations to the Akpol library manager to switch to a virtual library to implement a library based on technology and information systems. Through the modernisation of a virtual-based library system, it is hoped that a better learning environment can be created for cadets who can visit the library online and ease of access is expected to support efforts to improve the quality of education at Akpol, by following the rapid development of technology in the digital era can increase the insight of cadets.